Origins of a Southern Mosaic Studies of Early Carolina and Georgia - Mercantini, Jonathan (Mercer University Lamar Memorial Lectures, 1975)
Origins of a Southern Mosaic explores the distinct, individual, and separate states that made up the colonial South. This volume contains four expanded lectures delivered in 1974 by Clarence L. Ver Steeg, professor of history at Northwestern University, as part of the annual Lamar Memorial Lectures at Mercer University. These lectures offer insight into the unique political and social backgrounds of Georgia and the Carolinas and the ways in which the individual backgrounds of these states come together to form a "quilt-like mosaic," with identifiable enclaves that contribute a special quality to the whole. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.